2014
DOI: 10.1515/hf-2014-0054
|View full text |Cite
|
Sign up to set email alerts
|

Property enhancement of kenaf fiber composites by means of vacuum-assisted resin transfer molding (VARTM)

Abstract: This work was aimed at applying vacuumassisted resin transfer molding (VARTM) technique to reinforced polymer molding products made of vegetable fibers. Kenaf (Hibiscus cannabinus L. Malvaceae) bast fibers were preformed into mat by means of a cold press. The unsaturated polyester resin was infused into the preforms at a vacuum pressure of 1.3-1.6 kPa. The examination of the mechanical properties and microstructure of the prepared composites indicated that the modulus of elasticity (MOE), modulus of rapture (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…As the Fe content increased from 0% to 6.8%, 15.9% and 18.0%, MOE was decreased from 2,875MPa to 2,729MPa, 2,487MPa and 2,007MPa accordingly. Xia et al (2015) reported that, the MOE of the kenaf fiber-unsaturated polyester composites was 4,186 MPa, which was in the same range of these presented results.…”
Section: The Em Shielding Effectiveness Measurementsupporting
confidence: 87%
“…As the Fe content increased from 0% to 6.8%, 15.9% and 18.0%, MOE was decreased from 2,875MPa to 2,729MPa, 2,487MPa and 2,007MPa accordingly. Xia et al (2015) reported that, the MOE of the kenaf fiber-unsaturated polyester composites was 4,186 MPa, which was in the same range of these presented results.…”
Section: The Em Shielding Effectiveness Measurementsupporting
confidence: 87%
“…The composites were fabricated using the un-treated kenaf fibers, Kenaf/magnetite20, Kenaf/magnetite30, and Kenaf/magnetite40 through vacuum-assisted resin transfer molding (VARTM) process described in the previous research [43]. Briefly, the kenaf preform, with a dimension of 110 × 165 × 10 mm (width × length × thickness), was placed on the mold that was covered with a flexible polyethylene vacuum bag.…”
Section: Fabrication Of Compositesmentioning
confidence: 99%
“…However, in this work the MOE was significantly increased. It might be contributed to the VARTM process, which could enhance MOE considerably compared with the traditional hot-pressing process [43]. TE, TS, and TEB of the four types of composites are compared in Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Other potential applications for bast and core are reinforcements in bioplastics and biocomposites, biofuel production, and other chemical end-use products Inoue et al, 2007;. Particularly, numerous studies have highlighted the competitiveness of kenaf bast fibers in the production of reinforced polymer products, using vacuum-assisted resin transfer molding (Xia et al, 2016a;Xia et al, 2015b). It has also been pointed that a kenaf fiber/polyester composites can replace glass fiber in the automotive industry, when impregnated and treated for water resistance, and that mechanical properties are often dramatically enhanced (Xia et al, 2015a;Xia et al, 2015c;Xia et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%